PENGARUH SIKLUS KONVERSI KAS TERHADAP PROFITABILITAS PERUSAHAAN (Studi Pada Perusahaan Makanan dan Minuman yang Terdaftar di BEI Periode 20011- 2016) - Fajarani, Regilia Astri (Jurnal Ilmiah Mahasiswa FEB, 2018)
This research aims at finding out the effect of cash conversion cycle on a company's profitability as measured by Return on Assets (ROA) of food and beverage companies listed in the IDX. Food and beverage industry in Indonesia has been currently one of manufactures with significant growth. The companies’ sustainability depends much on the leadership quality in managing their cash conversion cycle for the sake of gaining optimum profit. The research population is the food and beverage companies listed in the IDX from 2011 up to 2016. The samples are 13 food and beverage companies listed during the period, making a total of 78 observations. The data are analysis by regression test. The results show that inventory period, account receivable period, and account payable period are significant variables which influence the companies’ profitability, as measured with ROA.  Keywords: Inventory period, Account receivable period, Account payable period, Return on Assets (ROA)